Macrostructure of hen egg from birds fed different levels of crude protein: Relación proteína-características físicas del huevo - Rodríguez-Ortega, Leodan Tadeo (Ecosistemas y Recursos Agropecuarios, 2021)
Crude protein (PC) content in feed is related to its cost and it can affect physical characteristics of the hen egg. The objective of this study was to evaluate the effect of decreasing levels of PC (18, 16, and 12 %) on variables associated to the macrostructure of hen egg. Each diet was randomly assigned to 10 replicates of five birds each. Second-cycle Bovans White hens aged 131 weeks were used. Fifteen samplings (one sampling every-other-day) were implemented during the experiment. In each sampling, three eggs were randomly selected from each replicate and diet. The following variables were evaluated in each egg: weight (P, g), length  (L, mm), width (A, mm), shape index (IF), volume (VOL, cm3), area (AR, cm2), albumen mass (MALB, g), yolk mass (MYEM, g), egg-shell mass (MCAS, g), albumen percentage (%ALB, %), yolk percentage (%YEM, %) and egg-shell percentage (%CAS, %). A total of 1,800 eggs, 600 per diet, were evaluated. Data were analyzed by linear models methodology. The diet with the lowest PC level (12 %) lead to lower values (P